Penetration testing essentials - Oriyano, Sean-Philip (Sybex, 2017)
IT Security certifications have stringent requirements and demand a complex body of knowledge. This essential guide lays the groundwork for any IT professional hoping to move into a cybersecurity career by developing a robust pen tester skill set.